(untitled) (Communications in Computational Physics, 2018)
In charge-stabilized colloidal suspensions, highly charged macroions, dressed by strongly correlated counterions, carry an effective charge that can be substantially reduced (renormalized) from the bare charge. Interactions between dressed macroions are screened by weakly correlated counterions and salt ions. Thermodynamic and structural properties of colloidal suspensions depend sensitively on the magnitudes of both the effective charge and the effective screening constant. Combining a charge renormalization theory of effective electrostatic interactions with Monte Carlo simulations of a one-component model, we compute osmotic pressures and pair distribution functions of deionized colloidal suspensions. This computationally practical approach yields close agreement with corresponding results from large-scale simulations of the primitive model up to modest electrostatic coupling strengths.